A qualitative exploration of Chinese rural older adults' adaption experience to disability in Henan Province - Mengke Gao; Yan Zhang; Yutong Tian; Yue Gao; Xiaohua Li; Yixin Lu (BMC, 2023)
Abstract Background The global population is ageing in a serious way and the number of disabled elderly people is increasing. Disability is a combination of physical and functional impairments, activity limitations, and social participation restrictions that significantly affect the quality of life of older adults. This study used the Roy adaptation model to examine the adaptive strategies of rural disabled elderly. Methods An interview outline was prepared based on the Roy Adaptation Model, in-depth interviews were conducted with eligible rural elderly with disabilities using purposive sampling. Interview data were analyzed using the colaizzi method to obtain relevant themes and sub-themes of the adaptation experience. Results Fifteen eligible disabled elderly participated in the interview, with an average age of 73.7 years old, showing different adaptation experiences in different aspects, a total of 5 themes and 18 sub-themes were extracted: (a)physiological function adaptation: learning to monitor physiological indicators, active medical compliance behavior, active rehabilitation exercise, adjusting lifestyle and coping with failure, (b) self-concept adaptation: adjustment of gratitude mentality, self-consolation, transferring the attention, seeking emotional comfort, and negative emotional response, (c) role function adaptation: positive self-care role, negative family role and escape of social role, (d) interdependence adaptation: actively seeking support and complex social coping, and (e) adaptation influencing factors: personal factors, caregiver factors and the policy factors. Conclusions The disabled elderly show different adaptation strategies in four ways, and are affected by personal factors, caregiver factors and policy factors. A multi-faceted support system for the disabled elderly is recommended, and the caregivers should be trained in all-round care knowledge and skills.